Systolic blood pressure and mortality in acute symptomatic pulmonary embolism - Quezada A; Jiménez D; Bikdeli B; Moores L; Porres-Aguilar M; Aramberri M; Lima J; Ballaz A; Yusen RD, Monreal M; RIETE investigators.; Monreal M; RIETE Investigators; Bosevski M; et al. (Elsevier, 2020)
Background: The optimal cutoff for systolic blood pressure (SBP) level to define high-risk pulmonary embolism (PE) remains to be defined. Methods: To evaluate the relationship between SBP levels on admission and mortality in patients with acute symptomatic PE, the current study included 39,257 consecutive patients with acute symptomatic PE from the RIETE registry between 2001 and 2018. Primary outcomes included all-cause and PE-specific 30-day mortality. Secondary outcomes included major bleeding and recurrent venous thromboembolism (VTE). Results: There was a linear inverse relationship between admission SBP and 30-day all-cause and PE-related mortality that persisted after multivariable adjustment. Patients in the lower SBP strata had higher rates of all-cause death (reference: SBP 110-129 mmHg) (adjusted odds ratio [OR] 2.9; 95% confidence interval [CI], 2.0-4.2 for SBP <70 mmHg; and OR 1.7; 95% CI, 1.4-2.1 for SBP 70-89 mmHg). The findings for 30-day PE-related mortality were similar (adjusted OR 4.4; 95% CI, 2.7-7.2 for SBP <70 mmHg; and OR 2.6; 95% CI, 1.9-3.4 for SBP 70-89 mmHg). Patients in the higher strata of SBP had significantly lower rates of 30-day all-cause mortality compared with the same reference group (adjusted OR 0.7; 95% CI, 0.5-0.9 for SBP 170-190 mmHg; and OR 0.6; 95% CI, 0.4-0.9 for SBP >190 mmHg). Consistent findings were also observed for 30-day PE-related death. Conclusions: In patients with acute symptomatic PE, a low SBP portends an increased risk of all-cause and PE-related mortality. The highest mortality was observed in patients with SBP <70 mmHg.
Keywords: Mortality; Pulmonary embolism; Systolic blood pressure